Comparing the B and T cell-mediated immune responses in patients with type 2 diabetes receiving mRNA or inactivated COVID-19 vaccines - Lee, Chi-Ho; Gray, Victor; Teo, Jia Ming Nickolas; Tam, Anthony Raymond; Fong, Carol Ho-Yi; Lui, David Tak-Wai; Pang, Polly; Chan, Kwok Hung; Hung, Ivan Fan-Ngai; Tan, Kathryn Choon-Beng; Ling, Guang Sheng (Frontiers in Immunology, 2022)
Acquiring protective immunity through vaccination is essential, especially for patients with type 2 diabetes who are vulnerable for adverse clinical outcomes during coronavirus disease 2019 (COVID-19) infection. Type 2 diabetes (T2D) is associated with immune dysfunction. Here, we evaluated the impact of T2D on the immunological responses induced by mRNA (BNT162b2) and inactivated (CoronaVac) vaccines, the two most commonly used COVID-19 vaccines. The study consisted of two parts. In Part 1, the sera titres of IgG antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) alpha receptor binding domain (RBD), their neutralizing capacity, and antigen-specific CD4+T and CD8+T cell responses at 3-6 months after vaccination were compared between BNT162b2 (n=60) and CoronaVac (n=50) vaccinees with or without T2D. Part 2 was a time-course study investigating the initial B and T cell responses induced by BNT162b2 among vaccinees (n=16) with or without T2D. Our data showed that T2D impaired both cellular and humoral immune responses induced by CoronaVac. For BNT162b2, T2D patients displayed a reduction in CD4+T-helper 1 (Th1) differentiation following their first dose. However, this initial defect was rectified by the second dose of BNT162b2, resulting in comparable levels of memory CD4+ and CD8+T cells, anti-RBD IgG, and neutralizing antibodies with healthy individuals at 3-6 months after vaccination. Hence, T2D influences the effectiveness of COVID-19 vaccines depending on their platform. Our findings provide a potential mechanism for the susceptibility of developing adverse outcomes observed in COVID-19 patients with T2D and received either CoronaVac or just one dose of BNT162b2.